Introduzindo o conceito de Média Aritmética na 4ª série do Ensino Fundamental, usando o ambiente computacional - Lima, Rosana Catarina Rodrigues de (2005)
The purpose of this study was to investigate the introduction of arithmetic mean concept based on the use of graphic representations, and with the assistance of computational environement by using the software Tabletop. To reach this purpose, a nearly experimental study has been accomplished with two groups of students, the experimental group GE and the control group GC both fourth graders of a Sao Paulo public school. The research was divided into three phases, namely: Pre-Test, Teaching Interference (experimental factor) and Post-Test. The activities composing the Teaching Interference have been adjusted to the Conceptual Fields Theory proposed by Vergnaud. To develop these activities we based on graphics understanding levels proposed by Curcio and on arithmetic mean properties proposed by Straus & Bichler. The GE has taken part in the three phases of the study seeing that the teaching interference activities, developed within computacional environment, aimed at both, the introduction of arithmetic mean concept and the graphics reading and interpretation development. The GC has also taken part in tests application, but it was left out the experimental factor. The study has intended to answer the following question: Which teaching interference contributions are proposed for the introduction of arithmetic mean concept into fourth graders , by making use of computational environment? To answer this research question, we based ourselves on qualified and quantified analysis of the results obtained from the tests in both groups and on the answers given by GE students to the activities cards of the intervention. By comparing the intergroups post-test results, one verify that the GE students have presented a better performance than the GC one s, specially regarding arithmetic mean concept. On the other hand, the analisys of the results within the groups pointed to an improvement in the post-test performed by the Experimental Group in respect to the pre-test, regarding the reading and interpretation of bar graphics, as well as in arithmetic mean concept. These data permit us to conclude that the introduction to arithmetic mean concept based on graphic representation has been favoured by the use of Tabletop software, since it allows the students to catch the proprieties and relations envolved in Conceptual Field formed by graphic reading and interpretation as well as arithmetic mean